Wards of the State : the long shadow of American foster care - Rowe, Claudia, 1966- (Abrams Press, 2025)
A compelling exploration of the broken American foster care system, told through the stories of six former foster youth. This powerful narrative nonfiction book delves into the systemic failures that lead many foster children into the criminal justice system, highlighting the urgent need for reform. ​This book is a must-read for anyone interested in child welfare, social justice, and the transformative power of the best narrative nonfiction. In Wards of the State, award-winning journalist Claudia Rowe's storytelling is both vivid and unflinching, offering readers a deep understanding of the foster care-to-prison pipeline. Through interviews with psychologists, advocates, judges, and the former foster children themselves, Rowe paints a heartbreaking picture of the lives shaped by this broken system. Rowe brings her extensive experience and investigative prowess to this eye-opening work. With a career spanning over 25 years, Rowe has written for publications such as The New York Times and Mother Jones, and her reporting has influenced policy changes in Washington State. Her previous book, The Spider and the Fly, was a gripping true-crime memoir that showcased her ability to blend personal narrative with broader social issues. By the time Maryanne was 16 years old, she had been arrested for murder. In and out of foster and adoptive homes since age 10, she'd run away, been trafficked and assaulted, and finally pointed a gun at the latest man to take her into his car. She pulled the trigger and fled. But with no family to turn to and few reliable friends, it didn't take long for the police to catch up with her. In court, the defense blamed neither traffickers, nor Maryanne, but Washington state itself--or rather, its foster care system, which parents thousands of children every year. The courts didn't listen to that argument, but award-winning journalist Claudia Rowe did. Washington state isn't alone. Each year, hundreds of thousands of children grow up in America's $30 billion foster care system, only to leave and enter its prisons, where a quarter of all inmates are former foster youth. Weaving Maryanne's story with those of five other foster kids across the country--including an 18-year-old sleeping on the New York City subways; a gangbanger turned graduate student; and a foster child who is now a policy advisor to the White House--Rowe paints a visceral survival narrative showing exactly where, when, and how the system channels children into locked cells.